Deinococcus radiodurans pprI expression enhances the radioresistance of eukaryotes - Wen, Ling (Oncotarget, 2016)
PprI accelerates radiation-induced DNA damage repair via regulating the expression of DNA repair genes and enhances antioxidative enzyme activity in Deinococcus radiodurans after radiation. The main aim of our study was to determine whether the expression of pprI gene could fulfil its DNA repair function in eukaryotes and enhance the radioresistance of eukaryotic organism or not. In this study, we constructed pEGFP-c1-pprI eukaryotic expression vector and established a human lung epithelial cell line BEAS-2B with stable integration of pprI gene. We found that pprIexpression enhanced radioresistance of BEAS-2B cells, decreased γ-H2AX foci formation and apoptosis in irradiated BEAS-2B cells and alleviated radiation induced G2/M arrest of BEAS-2B cells. Moreover, we transferred pEGFP-c1-pprI vector into muscle of BALB/c mice by in vivo electroporation and studied the protective effect of prokaryotic pprI gene in irradiated mice. We found that pprI expression alleviated acute radiation induced hematopoietic system, lung, small intestine and testis damage and increased survival rate of irradiated mice via regulating Rad51 expression in different organs. These findings suggest that prokaryotic pprI gene expression in mammalian cells could enhance radioresistance in vitro and in vivo.